2020
DOI: 10.3389/fchem.2020.582757
|View full text |Cite
|
Sign up to set email alerts
|

Supramolecular Encapsulation of a Neurotransmitter Serotonin by Cucurbit[7]uril

Abstract: pH-dependent host-guest complexation of a monoamine neurotransmitter, Serotonin, with cucurbit[7]uril has been thoroughly investigated. The binding phenomena were explored using steady-state and time-resolved fluorescence spectroscopy at different pH values. At lower pH, i.e., protonated Serotonin, the binding affinity with cucurbit[7]uril was significantly higher compared to higher pH. Furthermore, detailed NMR titration experiments depicted the solution structure of the host-guest complex through the complex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 53 publications
0
16
0
1
Order By: Relevance
“…Cyclodextrin has been reported to induce shape changes of the membrane internalization type on erythrocytes. CyDs can release cholesterol from the erythrocyte membrane, thereby causing hemolysis [13]. It is known that CB [7] and other homologues (with the exception of CB [5] and CB [6]) can also bind cholesterol molecules [31], so the hemolytic effect of cucurbiturils may be similar to the effects of cyclodextrins.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cyclodextrin has been reported to induce shape changes of the membrane internalization type on erythrocytes. CyDs can release cholesterol from the erythrocyte membrane, thereby causing hemolysis [13]. It is known that CB [7] and other homologues (with the exception of CB [5] and CB [6]) can also bind cholesterol molecules [31], so the hemolytic effect of cucurbiturils may be similar to the effects of cyclodextrins.…”
Section: Discussionmentioning
confidence: 99%
“…These data assert and allow using cucurbiturils as a remarkable drug delivery system. Special cases of the encapsulation by cucurbiturils of serotonin [13] and histamine H2 antagonists such as cimetidine, famotidine and nizatidine [14] in the 1:1 inclusion complex allow to expand the possibility of cucurbituril's application for various nosologies. Recently, it was reported that complexation CB [7] with chloroquine permits reducing its nonspecific toxicity over several rounds and improves its antiviral activity against coronavirus, confirming the pronounced synergistic effect of cucurbiturils.…”
Section: Introductionmentioning
confidence: 99%
“…27 Recently, the complexation of serotonin, a neurotransmitter, with CB7 has been reported. 28 The results indicated that CB7 forms a 1 : 1 inclusion complex with serotonin with a binding affinity of 2.3 × 10 4 M −1 .…”
Section: Introductionmentioning
confidence: 95%
“…E-mail: Khaleel.assaf@bau.edu.jo reported. 28 The results indicated that CB7 forms a 1 : 1 inclusion complex with serotonin with a binding affinity of 2.3 × 10 4 M −1 .…”
Section: Introductionmentioning
confidence: 95%
“…A desirable attribute of any supramolecular encapsulation mechanism is that the activity of the molecule being delivered should not be adversely affected because of administration through the delivery vehicle. The activity of various drugs delivered through supramolecular encapsulation in cucurbiturils has been found to have remained unchanged, showing that cucurbit­[ n ]­urils can act as efficient encapsulation and delivery agents. Recently, cucurbit[7]­uril (or CB7) (Figure ) has been used to conceal the bitter taste of denatonium benzoate, known to be the most bitter compound to humans, and has been evaluated in mice, where it was found that CB7 encapsulation can abolish the aversive response toward denatonium benzoate . Hence, we selected CB7 as a candidate macrocycle for the nanoencapsulation of bitter phytochemicals to be introduced into an insect model system.…”
Section: Introductionmentioning
confidence: 99%